2019
DOI: 10.1128/mbio.01617-19
|View full text |Cite|
|
Sign up to set email alerts
|

Hepatitis C Virus Infection Induces Hepatic Expression of NF-κB-Inducing Kinase and Lipogenesis by Downregulating miR-122

Abstract: Hepatitis C virus (HCV) harnesses host dependencies to infect human hepatocytes. We previously identified a pivotal role of IκB kinase α (IKK-α) in regulating cellular lipogenesis and HCV assembly. In this study, we defined and characterized NF-κB-inducing kinase (NIK) as an IKK-α upstream serine/threonine kinase in IKK-α-mediated proviral effects and the mechanism whereby HCV exploits this innate pathway to its advantage. We manipulated NIK expression in Huh7.5.1 cells through loss- and gain-of-function appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Therefore, it is clear that miR-122 participates in the differentiation of hepatoblasts towards hepatocytes; however, its activity also extends towards other processes. As was previously described, miR-122 plays a pivotal role in regulating hepatic gene expression, affecting various aspects of cellular activity such as response to oxidative stress [81], viral infection [82], inflammation [83], and even tumorigenesis, as its dysregulation has notoriously been reported as an viable marker of HCC onset and development [84,85]. miR-122 has also been described to orchestrate lipid metabolism; as Cheung et al [28] demonstrated in their study, miR-122 inhibition in healthy mice resulted in a decreased expression of hepatic de novo lipogenesis genes such as FASN (fatty acid synthase) and ACC1 (acetyl-CoA carboxylase), which encode two rate-limiting enzymes.…”
Section: Mir 122-5pmentioning
confidence: 89%
“…Therefore, it is clear that miR-122 participates in the differentiation of hepatoblasts towards hepatocytes; however, its activity also extends towards other processes. As was previously described, miR-122 plays a pivotal role in regulating hepatic gene expression, affecting various aspects of cellular activity such as response to oxidative stress [81], viral infection [82], inflammation [83], and even tumorigenesis, as its dysregulation has notoriously been reported as an viable marker of HCC onset and development [84,85]. miR-122 has also been described to orchestrate lipid metabolism; as Cheung et al [28] demonstrated in their study, miR-122 inhibition in healthy mice resulted in a decreased expression of hepatic de novo lipogenesis genes such as FASN (fatty acid synthase) and ACC1 (acetyl-CoA carboxylase), which encode two rate-limiting enzymes.…”
Section: Mir 122-5pmentioning
confidence: 89%
“…Here, miR-122 directly binds to the viral genome and enhances viral RNA replication, thus resulting in reduced miR-122 expression within the cell [115,116]. The NFκB-inducing kinase (NIK) is usually a target of miR-122, but due to the decreased levels of miR-122, NIK is increased in HCV infection [117]. In addition, HNF4α, a transcriptional regulator of miR-122 expression and known for its OS-association [118], is downregulated in HCV infection, too [117].…”
Section: Viral Hepatitismentioning
confidence: 99%
“…The NFκB-inducing kinase (NIK) is usually a target of miR-122, but due to the decreased levels of miR-122, NIK is increased in HCV infection [117]. In addition, HNF4α, a transcriptional regulator of miR-122 expression and known for its OS-association [118], is downregulated in HCV infection, too [117]. Both effects result in disturbance of the NIK mediated lipid metabolism and HCV-induced lipogenesis and lipid droplet formation [117,119].…”
Section: Viral Hepatitismentioning
confidence: 99%
“…Viruses likewise manipulate their host cell's lipid metabolism, for example human cytomegalovirus (CMV) induces an increase in fatty acid production to synthesize lipids for incorporation into the viral envelope (63). Hepatocytes infected by Hepatitis C virus (HCV) are forced to increase lipogenesis and gluconeogenesis to support viral particle production via sophisticated mechanisms involving viral proteins and interference with host miRNAs (64, 65). Since hepatocytes are vital in regulating systemic glucose and lipid homeostasis these manipulations by HCV lead to a significantly increased risk for patients to develop metabolic disorders.…”
Section: The Role Of Lipid Metabolism In the Regulation Of T Cell Resmentioning
confidence: 99%